(untitled) - BenDaniel, David J. (New York, 2002)
International M&A, Joint Ventures, and Beyond provides a graduate- and professional-level course on all aspects and types of international business deals. This accompanying workbook allows you to practice the specialized techniques and strategies associated with becoming a cross-border M&A expert without leaving the comfort of your desk or losing millions of dollars over misunderstood international M&A issues. This workbook–a perfect companion to the actual text–helps familiarize you with the ins and outs of international M&A in todays business environment. The International M&A, Joint Ventures, and Beyond Workbook offers practical discussion points that will help further your understanding of cross-border deal making. This indispensable, hands-on companion to International M&A, Joint Ventures, and Beyond: Doing the Deal, Second Edition strengthens your grasp of the most critical aspects of international M&A, with such tools as: Study questions and answers, Sample agreements and forms,..
Keywords: Consolidation and merger of corporations,Consolidation and merger of corporations,Joint ventures,Joint ventures,International business enterprises,International business enterprises; Finance,Law and legislation,Finance,Law and legislation,Finance,Law and legislation